2011
DOI: 10.1371/journal.pone.0016761
|View full text |Cite
|
Sign up to set email alerts
|

Transient Responses to NOTCH and TLX1/HOX11 Inhibition in T-Cell Acute Lymphoblastic Leukemia/Lymphoma

Abstract: To improve the treatment strategies of T-cell acute lymphoblastic leukemia/lymphoma (T-ALL), further efforts are needed to identify therapeutic targets. Dysregulated expression of HOX-type transcription factors occurs in 30–40% of cases of T-ALL. TLX1/HOX11 is the prototypical HOX-type transcription factor. TLX1 may be an attractive therapeutic target because mice that are deficient in TLX1 are healthy. To test this possibility, we developed a conditional doxycycline-regulated mouse model of TLX1-initiated T-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…TLX1 driven T-ALLs show a unique gene expression signature related to early cortical thymocytes with corresponding expression of CD1a, CD4 and CD8 surface marker proteins. Initial studies showed that TLX1 could immortalize murine hematopoietic precursors 2,3 , but its leukemic potential has only been fully established using TLX1 transgenic mouse models that develop clonal T-cell malignancies with a long latency 4,5 . These TLX1 induced murine T-cell tumors share common features with human TLX1 positive leukemia, including activation of Notch signaling, loss of the Bcl11b tumor suppressor gene and a transcriptional program that disrupts the mitotic checkpoint and induces aneuploidy during T-cell transformation 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLX1 driven T-ALLs show a unique gene expression signature related to early cortical thymocytes with corresponding expression of CD1a, CD4 and CD8 surface marker proteins. Initial studies showed that TLX1 could immortalize murine hematopoietic precursors 2,3 , but its leukemic potential has only been fully established using TLX1 transgenic mouse models that develop clonal T-cell malignancies with a long latency 4,5 . These TLX1 induced murine T-cell tumors share common features with human TLX1 positive leukemia, including activation of Notch signaling, loss of the Bcl11b tumor suppressor gene and a transcriptional program that disrupts the mitotic checkpoint and induces aneuploidy during T-cell transformation 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Notch1 mutations are almost uniformly identified in murine T-cell tumors that developed from TLX1 transgenic mice 4,5 . Therefore, NOTCH1 activation and aberrant expression of TLX1 are considered collaborative events in the multi-step pathogenesis of T-ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Murine models of TLX1 + T-ALL have provided support for this hypothesis. However, the long latency of T-cell tumor formation and clonal nature of the resulting malignancies indicated the requirement for additional mutations [10-13]. Multiple lines of investigation have implicated dysregulated expression of TLX1 target genes involved in the mitotic spindle assembly checkpoint that predispose to Chromosomal Instability (CIN) and aneuploidy, as contributing to TLX1-mediated leukemogenesis [12,14-16].…”
Section: Introductionmentioning
confidence: 99%
“…However, until recently, very little was known about the specific mechanisms that mediate T-cell transformation downstream of TLX1. Moreover, the generation of a mouse model of TLX1-induced T-ALL eluded the efforts of several groups over the past decade (15,16). In this context, the generation of an LCK-TLX1 transgenic mouse model that recapitulates the histologic, transcriptional, and genetic features of TLX1-induced T-ALL has provided a muchneeded tool for the analysis of the molecular and cellular mechanisms of TLX1-induced transformation (16).…”
Section: Introductionmentioning
confidence: 99%
“…The 6-month latency before the development of leukemia in LCK-TLX1 transgenic mice (15,16) and the observation that these tumors show clonal expression of the T-cell receptor b suggest that TLX1 overexpression may not be sufficient for T-cell transformation and that full leukemia development may depend on the acquisition of secondary cooperating mutations. The NOTCH1 signaling pathway plays a prominent role in T-ALL pathogenesis, with more than 50% of the patients harboring activating NOTCH1 mutations (17).…”
Section: Introductionmentioning
confidence: 99%